2023
DOI: 10.2215/cjn.0000000000000342
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Steady Glucose Concentration Peritoneal Dialysis on Ultrafiltration Volume and Sodium Removal

Olof Heimbürger,
Jörgen Hegbrant,
Giedre Martus
et al.

Abstract: Background Volume overload is common in peritoneal dialysis (PD) patients and is associated with poor clinical outcome. Steady concentration PD is where a continuous glucose infusion maintains the intraperitoneal glucose concentration and as a result provides continuous ultrafiltration throughout the dwell. The primary objective of this study was to investigate the ultrafiltration rate and glucose ultrafiltration efficiency for steady concentration PD in comparison with a standard continuous ambula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Recently reported findings showed that the method of steady-concentration PD performed using a device providing continuous glucose infusion to maintain a high intraperitoneal glucose concentration resulted in higher UF rates, more efficient use of glucose (increased ultrafiltration volume/gram glucose absorbed), and greater sodium removal than those when using standard 2.5% dextrose CAPD dwell ( Heimburger et al, 2023 ). However, while the strategy of PD with a steady glucose concentration means a more efficient use of glucose as an osmotic agent, it is associated with increased exposure to glucose, which may have disadvantages because of harmful metabolic effects and negative effects on the peritoneum.…”
Section: Discussionmentioning
confidence: 99%
“…Recently reported findings showed that the method of steady-concentration PD performed using a device providing continuous glucose infusion to maintain a high intraperitoneal glucose concentration resulted in higher UF rates, more efficient use of glucose (increased ultrafiltration volume/gram glucose absorbed), and greater sodium removal than those when using standard 2.5% dextrose CAPD dwell ( Heimburger et al, 2023 ). However, while the strategy of PD with a steady glucose concentration means a more efficient use of glucose as an osmotic agent, it is associated with increased exposure to glucose, which may have disadvantages because of harmful metabolic effects and negative effects on the peritoneum.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, such high-glucose exposure is not only detrimental to the PM (local bioincompatibility) but also has many potential systemic metabolic side effects (systemic bioincompatibility) such as insulin resistance, de novo diabetes, and cardiovascular (CV) disease [ 11 , 12 ]. A recent pilot study [ 13 ] showed that steady-concentration PD, performed with the Carry Life UF device (Triomed AB, Lund, Sweden) by adding glucose step-by-step (to maintain the glucose concentration in the PD solution) to a 1.5% glucose-based PD fluid resulted in higher UF rates, and in greater sodium removal compared to a 2.5% dextrose control PD dwell. This novel approach might effectively reduce the amount of glucose in the PD solution, although the extent/magnitude of such a reduction is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…This is the approach that has been adopted by TrioMed, and in this issue of CJASN, they demonstrate proof of this principle in an elegantly designed dose-finding study. 4 Using a cross-over study design, they report the ultrafiltration and sodium removal achieved during typical CAPD length dwells (5 hours) in eight patients, using three different glucose infusion protocols, and compare these with a standard 2.27% glucose/2.5% dextrose 4-hour exchange and a prior overnight icodextrin exchange. The glucose infusion protocol requires an additional 50% glucose concentration bag, which is attached to a portable device that can drip feed glucose into the peritoneal cavity, thus holding the intraperitoneal glucose concentration steady throughout the dwells.…”
mentioning
confidence: 99%
“…This is the approach that has been adopted by TrioMed, and in this issue of CJASN , they demonstrate proof of this principle in an elegantly designed dose-finding study. 4…”
mentioning
confidence: 99%